LEADERSHIP STYLES AND EMPLOYEE PERFORMANCE IN MULTINATIONAL CORPORATIONS - R.Taufiq Nur M; Elida Zia‘ul Huda (CV. Adiba Aisha Amira, 2026)
Multinational companies face complex challenges in managing human resources who come from various cultural backgrounds, values ​​and work systems. One important factor that influences the success of management is leadership style. This research aims to comprehensively examine the relationship between leadership style and employee performance in multinational companies through a literature review approach. The research method used is qualitative research by reviewing reputable national and international journals, textbooks and scientific publications related to leadership and employee performance. The study results show that various leadership styles, such as transformational, transactional, authentic, situational and cross-cultural leadership, have a significant influence on employee performance. The effectiveness of leadership style is greatly influenced by the cultural context, organizational system, and the role of mediating variables such as job satisfaction and organizational commitment. This study concludes that implementing a leadership style that is adaptive and sensitive to cultural differences can improve employee performance in a sustainable manner in multinational companies. It is hoped that the findings of this research can provide theoretical contributions in the development of global leadership studies as well as practical implications for the management of multinational companies.